Aging in China Implications to Social Policy of a Changing Economic State - Chen, Sheying; Powell, Jason L.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2012)
Aging in China Implications to Social Policy of a Changing Economic State Sheying Chen and Jason L. Powell, editors China$1 (Bs elder population is on the rise$1 (Bat a faster rate than anywhere else on the globe, and with fewer young people to support them. These statistics are of no small importance to a nation growing in economic power and world status, or to those looking to China for a deeper understanding of an aging world. Aging in China examines the current picture and future challenges in light of the steps being taken toward comprehensive elder policy after decades of the One Child Law. Approaching China$1 (Bs complex social policy landscape through conceptual, theoretical, and empirical perspectives, expert contributors analyze critical issues regarding pensions, long-term care, housing, caregiver burden, care inequities between urban and rural sectors, and the economics of providing for a burgeoning population of older people. Included in the coverage: The development of income security policies for the elderly. Social policy, family support, and rural elder care. Gendered social capital and health outcomes among older adults. An East/West approach to mind-body health among Chinese elders. Family caregiving and its impact on caregiver mental health. The evolution of Chinese nonprofit organizations and elder care homes. As a core resource for nation-specific or comparative study, Aging in China will interest readers across a wide range of disciplines, including gerontologists, sociologists, cross-cultural and health psychologists, and public health policymakers.s
Chapter 1. Introduction: Social Policy of the Changing Economic State -- Chapter 2. China and the Bio medicalization of Aging: Implications and Possibilities -- Chapter 3. Aging: The Role of Work and Workplace Implications - Changing Expectations in the US and China -- Chapter 4. Pensions and Social Assistance: The Development of Income Security Policies for Old People in China -- Chapter 5. Rural Old Age Support in Transitional China: Efforts between Family and State -- Chapter 6. Social Policy, Family Support, and Rural Elder Care -- Chapter 7. China$1 (Bs Family Support System: Impact of Rural-Urban Female Labor Migration -- Chapter 8. The Utility of Enhancing Filial Piety for Eldercare in China -- Chapter 9. Gendered Social Capital and Health Outcomes among Older Adults in China -- Chapter 10. An East-West Approach to Mind-Body Health of Chinese Elderly -- Chapter 11. Family Caregiving and Impact on Caregiver Mental Health: A Study in Shanghai -- Chapter 12. Housing Stratification and Aging in Urban China -- Chapter 13. Institutional Care -- Chapter 14. Chaning Welfare Institution and Evolution of Chinese Nonprofit Organizations: The Story of Elder Care Homes in Urban Shanghai -- Chapter 15. Aging Policy Integrative Appraisal System (Apias) in the Asia Pacific Region: A Case Study on Macao Special Administrative Region.s
Keywords: Social sciences; Quality of Life; Social policy; Aging -- Research; Quality of Life -- Research; Social Sciences; Aging; Social Policy; Public Health/Gesundheitswesen.; Quality of Life Research